THE INFLUENCE OF ANCIENT CIVILIZATIONS OF CENTRAL ASIA ON THE FORMATION OF UZBEK ETHNIC IDENTITY - Sattorov Nurbek Abdurazzokovych; Salimova Zebuniso Ilhom qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the influence of ancient Central Asian civilizations on the formation of Uzbek ethnic identity. By analyzing archaeological, historical, and anthropological evidence, the study highlights how the legacy of early cultures such as the Sogdians, Bactrians, and Khwarezmians, among others, contributed to the ethnic and cultural foundation of the Uzbek people. The study examines the continuity of cultural elements including language, art, and social structures inherited from these ancient civilizations and how they shaped the distinctive identity of the Uzbek nation. In addition, the impact of external influences such as trade routes, migrations, and conquests is considered in the complex process of ethnogenesis. Our article concludes with a discussion of how modern scientific approaches such as genetic studies and archaeological discoveries provide new insights into the historical development of the Uzbek people.